Conflict management beyond the judicial way: Considerations and reflection - Erlo , Gustavo; Espelho , Aleandro; Gentil, Plínio (Seven Editora, 2023)
The present article deals with two means of resolving two conflicts other than the orbit of the judicial decision – such as, for example, it can be the files of conciliation, mediation, and arbitration - and its non-daily applicability to both cities, as well as how these practices are seen Profissionais hairs do Direito and possíveis usuários own hairs. It seeks to briefly analyze two consensual methods of conflict resolution through extrajudicial interference and how, effectively and technically, these can operate in the construction of a less violent society, without outlining the difficulties and resistance encountered for its concretization of fact, a social and economic context that is placed as the basis of action of the impartial third party, conflict solver. DOI: https://doi.org/10.56238/devopinterscie-105